Work Ethic Values in Pappaseng and its Implications for Career Guidance in Schools - Syahril, Syahril (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2018)
The aims of this study was to reveal the work ethic values in the Bugis tribal pappaseng and the implications of work ethic values in pappaseng in career guidance. This type of research is descriptive qualitative research. The location of the study was conducted in Bone and Wajo District, South Sulawesi. Data collection is done through interviews with the number of respondents as many as four people consisting of two cultural people, one community leader and one academic. The results showed that Pappaseng reso, getteng, lempu, green tea idi’pa najaji, sipakainge, sipakatau, sipakalebbi, sipakainge malilu, mali siparappe, rebba sipatokkong, and siri were work ethic values in pappaseng which had implications for the development of career guidance services for student.